The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/gcb.12845
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and tipping points of an exploited fish population over six decades

Abstract: Complex natural systems with eroded resilience, such as populations, ecosystems and socio-ecological systems, respond to small perturbations with abrupt, discontinuous state shifts, or critical transitions. Theory of critical transitions suggests that such systems exhibit fold bifurcations featuring folded response curves, tipping points and alternate attractors. However, there is little empirical evidence of fold bifurcations occurring in actual complex natural systems impacted by multiple stressors. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 69 publications
(148 reference statements)
1
71
0
Order By: Relevance
“…Although there is increased emphasis on complex ecological processes and environmental forcing (Rice ), a growing body of literature demonstrating nonlinear relationships and tipping points (Glaser et al . ; Vasilakopoulos and Marshall ; Hunsicker et al . ) and increased recognition of the importance of resilience to natural resource management (Polasky et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is increased emphasis on complex ecological processes and environmental forcing (Rice ), a growing body of literature demonstrating nonlinear relationships and tipping points (Glaser et al . ; Vasilakopoulos and Marshall ; Hunsicker et al . ) and increased recognition of the importance of resilience to natural resource management (Polasky et al .…”
Section: Introductionmentioning
confidence: 99%
“…The spawning stock-recruitment relationship is a fundamental and challenging problem in fisheries science and at the centre of a current debate on drivers of stock productivity and productivity regime shifts (Vert-pre et al 2013;Klaer et al 2015;Szuwalski et al 2015;Porch and Lauretta 2016). Although there is increased emphasis on complex ecological processes and environmental forcing (Rice 2011), a growing body of literature demonstrating nonlinear relationships and tipping points (Glaser et al 2014;Vasilakopoulos and Marshall 2015;Hunsicker et al 2016) and increased recognition of the importance of resilience to natural resource management (Polasky et al 2011;Brown and Williams 2015), we lack an eco-evolutionary framework to understand drivers of adult abundance in marine fish. As noted by Phil Levin in his 1989 Robert H. MacArthur award lecture (Levin 1992), 'the chasm between evolutionary biology and ecosystems science is a wide one.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 1d, the possible system states are arbitrarily divided into three classes, i.e., Classes 1, 2, and 3. As shown in Figure 1d, shifts across classes (which can be smooth, abrupt, or discontinuous) (see details in Collie et al, 2004, Collie et al, 2004, and Vasilakopoulos & Marshall, 2015 occur at indicated threshold levels of the driver, i.e., π T,1 , π T,2 , and π T,3 . The regime will be driven from Class 1 to Class 2 when the driver is decreased below π T,2 ; it will be driven further to Class 3 when the driver is decreased below π T,1 .…”
Section: Eco-resiliencementioning
confidence: 99%
“…Such regime shifts have arguably taken place regarding the ways in which the Kola winter temperature and the HSI series and their interplay have developed. For a general biological account of regime shifts in relation to climate changes, also of relevance for the NEA cod, see Brander (2010) and Vasilakopoulos and Marshall (2015).…”
Section: Regime Shifts and Structural Changesmentioning
confidence: 99%
“…Apparently, HSI bulk and Kola temperature patterns started to depart in the 1980s (Kjesbu et al 2014a, their figure 6: 9-year smoothed mean). Vasilakopoulos and Marshall (2015) identified a regime shift having taken place in 1981 using principal component analyses on 13 NEA cod population descriptors (including HSI) and five "stressors" (including Kola temperature). Hence, the outcome very much depends on the level of collated information and the statistical analyses undertaken.…”
Section: Regime Shifts and Structural Changesmentioning
confidence: 99%